3(x-4)8x=13

Simple and best practice solution for 3(x-4)8x=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)8x=13 equation:



3(x-4)8x=13
We move all terms to the left:
3(x-4)8x-(13)=0
We multiply parentheses
24x^2-96x-13=0
a = 24; b = -96; c = -13;
Δ = b2-4ac
Δ = -962-4·24·(-13)
Δ = 10464
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{10464}=\sqrt{16*654}=\sqrt{16}*\sqrt{654}=4\sqrt{654}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-96)-4\sqrt{654}}{2*24}=\frac{96-4\sqrt{654}}{48} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-96)+4\sqrt{654}}{2*24}=\frac{96+4\sqrt{654}}{48} $

See similar equations:

| a+⅓=7/6 | | 2x5+x+5=180 | | x+17.8=32.4 | | 23-3b=5 | | 56=7(n-84) | | v-55/3=8 | | 2j+14=28 | | 18=4j+2 | | 3z-1=z-5 | | 3x−12=2(x−5) | | 8p+9+7p=8p+9+7p | | 2(x−7)=x−4 | | -2x+3(3x-11)=30 | | z-19=-9 | | 3(t)=-16t2+96t+112 | | 3+y/y+7=35 | | x+3=−x−5 | | 31/2x-53/4+2x=13/4x | | 5^.5x+12=21 | | 8m-2m+9=3m+15 | | 2e+8+e=e-12 | | 2g+22=6g+32 | | 3x(8)=2x(4) | | (3c+12)+2c=3c+(12+2c) | | (3c+12)+2c=3c+(12+2c | | (D^2+5D+4)=3-2x | | -(-6x+8)=5(x-1) | | 1/2y-10=1/6y | | 1/2(4a+6)=15 | | t/5+4=20 | | 24=6w-2w | | 3y+22=43 |

Equations solver categories